An Outbreak of USA300 Methicillin-Resistant Staphylococcus aureus Among People With HIV in Japan. (15th October 2020) - Ikeuchi, Kazuhiko; Adachi, Eisuke; Sasaki, Takashi; Suzuki, Masato; Lim, Lay Ahyoung; Saito, Makoto; Koga, Michiko; Tsutsumi, Takeya; Kido, Yasutoshi; Uehara, Yuki; Yotsuyanagi, Hiroshi
Abstract: Background: USA300 produces Panton-Valentin leucocidin (PVL) and is known as a predominant community-associated methicillin-resistant Staphylococcus aureus (MRSA) strain in the United States, but it was extremely rare in Japan. We report here an outbreak of USA300 in people with HIV (PWH) in Tokyo, Japan. Methods: We analyzed the cases of PVL-MRSA infection between 2010 and 2020 and screened for nasal colonization of PVL-MRSA in PWH who visited an HIV/AIDS referral hospital from December 2019 to March 2020. Whole-genome sequencing-based single nucleotide polymorphism (SNP) analysis was performed on these isolates. Results: During the study period, a total of 21 PVL-MRSA infections in 14 patients were identified after 2014. The carriage prevalence was 4.3% (12/277) and PVL-MRSA carriers were more likely to have sexually transmitted infections (STIs) within a year compared with patients who had neither a history of PVL-MRSA infection nor colonization (33.3% [4/12] vs 10.1% [26/258]; P  = .03). SNP analysis showed that all 26 isolates were ST8-SCC mec IVa-USA300. Twenty-four isolates were closely related (≤100 SNP differences) and had the nonsynonymous SNPs associated with carbohydrate metabolism and antimicrobial tolerance. Conclusions: An outbreak of USA300 has been occurring among PWH in Tokyo and a history of STI was a risk of colonization. Abstract : We reported that community-associated MRSA was emerging among people with HIV in Tokyo. SNP analysis showed that the outbreak was caused by ST8-SCC mec IVa-USA300, which was extremely rare in Japan. USA300 could be transmitted by sexual contact in Japan.